2017
DOI: 10.1200/jco.2017.35.4_suppl.606
|View full text |Cite
|
Sign up to set email alerts
|

Signet ring cell colorectal cancer: Genomic insights into a rare subpopulation of colorectal adenocarcinoma.

Abstract: 606 Background: Colorectal signet ring cell carcinoma (SRCC) has been shown to be associated with advanced tumor stage at presentation and worse outcomes. Due to the rarity of this subtype, 1% of all colorectal adenocarcinoma (CRC), little is known about its molecular characteristics. We aimed to characterize the molecular alterations of this subgroup. Methods: Metastatic CRC (mCRC) patients (pts) with signet ring cell (SC) histology who had tumors evaluated with next generation sequencing between February 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…SRC is de ned by the presence of ≥ 50% of tumour cells with intracytoplasmic mucin. It has been reported that compared with MAC, patients with SRC were more frequently associated with metastatic disease, metastases at multiple sites, and had a poorer survival than MAC patients [24,25]. Interestingly, during the follow-up period of 32 months, one SRCC patient did not experience any tumor recurrence.…”
Section: Discussionmentioning
confidence: 91%
“…SRC is de ned by the presence of ≥ 50% of tumour cells with intracytoplasmic mucin. It has been reported that compared with MAC, patients with SRC were more frequently associated with metastatic disease, metastases at multiple sites, and had a poorer survival than MAC patients [24,25]. Interestingly, during the follow-up period of 32 months, one SRCC patient did not experience any tumor recurrence.…”
Section: Discussionmentioning
confidence: 91%